High-speed copper-clad plate resin mixture and preparation method thereof
By modifying nano-silica, aliphatic epoxy resin, and polyethylene glycol diglycidyl ether, the problem of balancing toughness and thermal stability in traditional copper clad laminate resin mixtures was solved, resulting in high-performance copper clad laminate materials with a wide temperature range.
Patent Information
- Application Number
- CN202511365974.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-11-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional resin mixtures used in high-speed copper clad laminates struggle to balance toughness and thermal stability. The addition of toughening resins can improve material toughness but decrease thermal stability.
The material is modified by double grafting with modified nano-silica, aliphatic epoxy resin, and polyethylene glycol diglycidyl ether. Nano-silica serves as a physical reinforcing phase to restrict the thermal movement of the resin matrix, while the rigid structure of the aliphatic epoxy resin and the crosslinking network of polyethylene glycol diglycidyl ether enhance the mechanical properties and thermal stability of the material.
It maintains excellent thermal stability and mechanical properties over a wide temperature range, while also possessing high peel strength and low dielectric loss, meeting the dimensional stability and signal integrity requirements of high-frequency and high-speed copper-clad laminates.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of electronic materials, in particular to a resin mixture for high-speed copper-clad plate and a preparation method thereof. BACKGROUND
[0002] As the basis of the electronic industry, the performance of copper-clad plate often determines the performance of the finished product. A major factor affecting the performance of copper-clad plate is the resin system. Different resin systems can give copper-clad plate different properties. At present, epoxy resin is the largest type of resin used in the copper-clad plate industry.
[0003] Patent technology document CN112079978B discloses a DCPD-bisphenol type benzoxazine resin and a composition for copper-clad plate and a preparation method thereof. The composition for copper-clad plate is composed of DCPD-bisphenol type benzoxazine resin, naphthalene ring epoxy resin, maleimide resin, phosphorus-containing phenolic resin, imidazole catalyst and butanone. It has the characteristics of low dielectric constant, low dielectric loss and high heat resistance, and is especially suitable for use as raw material for copper-clad plate. At present, compared with ordinary FR-4 grade substrate, this type of copper-clad plate has better electrical performance and can meet the demand of terminal for mid loss. When paired with ordinary HTE type copper foil, the dielectric loss is low. If paired with RTF type copper foil or copper foil with lower surface roughness, the dielectric loss can be further reduced. However, adding a large amount of modified benzoxazine resin and DCPD type epoxy resin will cause the toughness of the substrate to drop sharply, thereby affecting its service life. Adding toughening resin can improve the toughness, but due to the structure of the toughening resin, the thermal stability of the material will be adversely affected. SUMMARY
[0004] Therefore, the purpose of the present application is to provide a resin mixture for high-speed copper-clad plate and a preparation method thereof, so as to solve the problem that the toughness and thermal stability of the traditional resin mixture for high-speed copper-clad plate are difficult to balance.
[0005] In order to achieve the above purpose, the present application provides a resin mixture for high-speed copper-clad plate, which is prepared from the following raw materials in parts by weight: 60 parts of acetone, 140 parts of cyclohexanone, 10-50 parts of BNE type epoxy resin, 15-30 parts of DCPD type epoxy resin, 15-30 parts of acid anhydride curing agent, 200-250 parts of fused silica, 30-80 parts of toughening resin, 10-15 parts of modified nano-silicon dioxide, 45-55 parts of phenolic resin, 35-100 parts of phosphorus-containing flame retardant, 0-15 parts of phosphazene, and 0.09-0.11 parts of accelerator. The preparation steps of the modified nano-silicon dioxide are as follows: S1: hydrolysis condensation of nano-silica and silane coupling agent KH-550 in a mixed solution of anhydrous ethanol and deionized water under a nitrogen atmosphere to obtain aminated nano-silica; S2: ring-opening addition reaction of aminated nano-silica and polyethylene glycol diglycidyl ether and aliphatic cyclic epoxy resin in anhydrous ethanol under a nitrogen atmosphere to obtain modified nano-silica.
[0006] The amount ratio of the nano-silica, silane coupling agent KH-550, anhydrous ethanol, and deionized water in step S1 is 10-15 g: 1-1.5 g: 150-160 mL: 40-50 mL.
[0007] The average thickness of the nano-silica in step S1 is <100 nm, the flake diameter is 1-3 um, and the specific surface area is 30 m 2 / g.
[0008] The amount ratio of the aminated nano-silica, polyethylene glycol diglycidyl ether, aliphatic cyclic epoxy resin, and anhydrous ethanol in step S2 is 10-15 g: 2-3 g: 1-1.5 g: 200-250 mL.
[0009] Preferably, the average molecular weight of the polyethylene glycol diglycidyl ether in step S2 is 400-500.
[0010] Preferably, the type of the aliphatic cyclic epoxy resin in step S2 is ERL-4221.
[0011] Preferably, the reaction conditions of the ring-opening addition reaction in step S2 are refluxing at 78-82℃ for 8-10 h.
[0012] Preferably, the type of the BNE type epoxy resin is CN704.
[0013] Preferably, the type of the anhydride curing agent is EF-30.
[0014] Preferably, the type of the fused silica is FS1002.
[0015] Preferably, the type of the toughening resin is 97103.
[0016] Preferably, the type of the phenolic resin is PF8020.
[0017] Preferably, the type of the phosphorus-containing flame retardant is PF8724.
[0018] Preferably, the type of the phosphazene is D990.
[0019] Preferably, the type of the accelerator is 2-MI.
[0020] Further, the application also provides a preparation method of the high-speed copper-clad plate resin mixture, and the specific steps are as follows: At room temperature, acetone, cyclohexanone, BNE type epoxy resin, DCPD type epoxy resin, acid anhydride curing agent are mixed, stirred uniformly, then fused silica is added, stirred uniformly, then toughening resin, modified nano-silica, phenolic resin, phosphorus-containing flame retardant are stirred uniformly, finally phosphazene and accelerator are added, stirred uniformly, to obtain the high-speed copper-clad plate resin mixture.
[0021] The high-speed copper-clad plate resin mixture of the application has the following beneficial effects: by adding nano-silica, on the one hand, the nano-silica can serve as a physical reinforcing phase to improve the mechanical properties of the material, and on the other hand, the nano-silica can be embedded in the resin matrix as a barrier to limit the movement of surface flexible chains, thereby showing a more excellent thermal expansion inhibition effect.
[0022] The application realizes the double graft modification of the aliphatic ring epoxy resin and the polyethylene glycol diglycidyl ether, the rigid cyclic structure of the aliphatic ring epoxy resin effectively inhibits the thermal motion of the molecular chain segment through the steric hindrance effect, forms a close interface with the nano-silica, thereby significantly reducing the thermal expansion coefficient of the material and improving the dimensional stability; the flexible chain segment of the polyethylene glycol diglycidyl ether constructs an enhanced crosslinking network with the resin matrix through the terminal epoxy groups, and the molecular synergistic effect of the rigid aliphatic ring and the flexible polyethylene glycol chain segment not only maintains the high rigidity characteristics of the material, but also improves the bending strength through the stress buffering mechanism, realizing the effect of rigidity and flexibility.
[0023] The high-speed copper-clad plate resin mixture of the application not only ensures the toughness, but also shows excellent thermal stability in the wide temperature range of 50-260 DEG C, solves the problem of the decrease of the thermal stability of the traditional copper-clad plate resin composition caused by the addition of the toughening resin, and at the same time, has high peel strength, low dielectric loss and good mechanical properties, fully meeting the strict requirements of high-frequency high-speed copper-clad plates on dimensional stability, signal integrity and reliability. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the application more clear and explicit, the application is further described in detail below in combination with specific examples.
[0025] The sources or properties of the raw materials used in the examples and comparative examples of the application are as follows: Nanosilica: average thickness <100 nm, flake diameter 1-3 um, purchased from Beijing Deke Island Gold Technology Co., Ltd.; polyethylene glycol diglycidyl ether: average molecular weight 400-500; the type of the aliphatic cyclic epoxy resin: ERL-4221; BNE type epoxy resin: type CN704; anhydride curing agent: type EF-30; fused silica: type FS1002; toughening resin: type 97103; phenolic resin: type PF8020; phosphorus-containing flame retardant: type PF8724; phosphazene: type D990; accelerator: type 2-MI.
[0026] Example 1: A high-speed copper-clad plate resin mixture, the specific preparation steps are as follows: (1) Under a nitrogen atmosphere, 10 g of nanosilica, 1 g of silane coupling agent KH-550, 150 mL of anhydrous ethanol and 50 mL of deionized water were added to the reaction kettle, and refluxed at 78°C for 3 h. After the reaction was completed, centrifugal washing, vacuum drying, and obtaining aminated nanosilica; (2) Under a nitrogen atmosphere, 10 g of aminated nanosilica was dispersed in 200 mL of anhydrous ethanol, then 2 g of polyethylene glycol diglycidyl ether and 1 g of aliphatic cyclic epoxy resin were added dropwise to the reaction system, and refluxed at 100°C for 8 h. After the reaction was completed, centrifugal washing, and methanol centrifugal, finally drying at 100°C for 12 h, obtaining modified nanosilica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 50 g of BNE type epoxy resin, 30 g of DCPD type epoxy resin, 15 g of anhydride curing agent were mixed, stirred for 50 min, then 125 g of fused silica was added, stirred for 50 min, then 125 g of fused silica was added again, stirred for 50 min, then 30 g of toughening resin, 10 g of modified nanosilica, 35 g of phosphorus-containing flame retardant were added, stirred for 50 min, finally 15 g of phosphazene and 0.09 g of accelerator were added, stirred for 110 min, obtaining a high-speed copper-clad plate resin mixture.
[0027] Example 2: A high-speed copper-clad plate resin mixture, the specific preparation steps are as follows: (1) Under a nitrogen atmosphere, 13 g of nanosilica, 1.3 g of silane coupling agent KH-550, 160 mL of anhydrous ethanol and 40 mL of deionized water were added to the reaction kettle, and refluxed at 80°C for 4 h. After the reaction was completed, centrifugal washing, vacuum drying, and obtaining aminated nanosilica; (2) Under the atmosphere of nitrogen, 13 g of aminated nano-silica was dispersed in 230 mL of anhydrous ethanol, then 2.5 g of polyethylene glycol diglycidyl ether and 1.3 g of aliphatic cyclic epoxy resin were added dropwise into the reaction system, and refluxed at 110°C for 9 h. After the reaction was completed, centrifugal washing was performed, and centrifugal washing with methanol was performed, and finally drying at 100°C for 12 h to obtain modified nano-silica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 10 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, then 100 g of fused silica was added, stirred for 60 min, then 100 g of fused silica was added again, stirred for 60 min, then 80 g of toughening resin, 13 g of modified nano-silica, 55 g of phenolic resin, 80 g of phosphorus-containing flame retardant were added, stirred for 60 min, and finally 15 g of phosphazene and 0.1 g of accelerator were added, stirred for 120 min to obtain a high-speed copper-clad plate resin mixture.
[0028] Example 3: A high-speed copper-clad plate resin mixture, the specific preparation steps are as follows: (1) Under the atmosphere of nitrogen, 15 g of nano-silica, 1.5 g of silane coupling agent KH-550, 160 mL of anhydrous ethanol and 50 mL of deionized water were added into the reaction kettle, and refluxed at 82°C for 4 h. After the reaction was completed, centrifugal washing was performed, and vacuum drying was performed to obtain aminated nano-silica; (2) Under the atmosphere of nitrogen, 15 g of aminated nano-silica was dispersed in 250 mL of anhydrous ethanol, then 3 g of polyethylene glycol diglycidyl ether and 1.5 g of aliphatic cyclic epoxy resin were added dropwise into the reaction system, and refluxed at 120°C for 10 h. After the reaction was completed, centrifugal washing was performed, and centrifugal washing with methanol was performed, and finally drying at 100°C for 12 h to obtain modified nano-silica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 15 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 70 min, then 100 g of fused silica was added, stirred for 70 min, then 100 g of fused silica was added again, stirred for 70 min, then 80 g of toughening resin, 15 g of modified nano-silica, 45 g of phenolic resin, 100 g of phosphorus-containing flame retardant were added, stirred for 70 min, and finally 0.11 g of accelerator was added, stirred for 110-130 min to obtain a high-speed copper-clad plate resin mixture.
[0029] Example 4: A high-speed copper-clad plate resin mixture, the specific preparation steps are as follows: (1) Under the atmosphere of nitrogen, 15 g of nano-silica, 1.5 g of silane coupling agent KH-550, 160 mL of anhydrous ethanol and 50 mL of deionized water were added into a reaction kettle, and refluxed at 80°C for 4 h. After the reaction was completed, centrifugal washing and vacuum drying were performed to obtain amino-modified nano-silica; (2) Under the atmosphere of nitrogen, 15 g of amino-modified nano-silica was dispersed in 250 mL of anhydrous ethanol, and then 2 g of polyethylene glycol diglycidyl ether and 1.5 g of aliphatic cyclic epoxy resin were added dropwise into the reaction system, and refluxed at 120°C for 10 h. After the reaction was completed, centrifugal washing and methanol centrifugal washing were performed, and finally dried at 100°C for 12 h to obtain modified nano-silica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 30 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, and then 100 g of fused silica was added, stirred for 60 min, and then 100 g of fused silica was added again, stirred for 60 min, and then 80 g of toughening resin, 13 g of modified nano-silica, 45 g of phenolic resin, 100 g of phosphorus-containing flame retardant were added, stirred for 60 min, and finally 0.1 g of accelerator was added, stirred for 120 min to obtain a high-speed copper-clad plate resin mixture.
[0030] Comparative Example 1: The difference from Example 2 is that no aliphatic cyclic epoxy resin is grafted, and the specific steps are as follows: (1) Under the atmosphere of nitrogen, 13 g of nano-silica, 1.3 g of silane coupling agent KH-550, 160 mL of anhydrous ethanol and 40 mL of deionized water were added into a reaction kettle, and refluxed at 80°C for 4 h. After the reaction was completed, centrifugal washing and vacuum drying were performed to obtain amino-modified nano-silica; (2) Under the atmosphere of nitrogen, 13 g of amino-modified nano-silica was dispersed in 230 mL of anhydrous ethanol, and then 2.5 g of polyethylene glycol diglycidyl ether was added dropwise into the reaction system, and refluxed at 110°C for 9 h. After the reaction was completed, centrifugal washing and methanol centrifugal washing were performed, and finally dried at 100°C for 12 h to obtain modified nano-silica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 10 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, and then 100 g of fused silica was added, stirred for 60 min, and then 100 g of fused silica was added again, stirred for 60 min, and then 80 g of toughening resin, 13 g of modified nano-silica, 55 g of phenolic resin, 80 g of phosphorus-containing flame retardant were added, stirred for 60 min, and finally 15 g of phosphazene and 0.1 g of accelerator were added, stirred for 120 min to obtain a high-speed copper-clad plate resin mixture.
[0031] Comparative Example 2: The difference from Example 2 is that polyethylene glycol diglycidyl ether is not grafted, and the specific preparation steps are as follows: (1) Under a nitrogen atmosphere, 13 g of nano-silica, 1.3 g of silane coupling agent KH-550, 160 mL of anhydrous ethanol, and 40 mL of deionized water were added to a reaction kettle, and refluxed at 80°C for 4 h. After the reaction was completed, centrifugal washing and vacuum drying were performed to obtain amino-modified nano-silica; (2) Under a nitrogen atmosphere, 13 g of amino-modified nano-silica was dispersed in 230 mL of anhydrous ethanol, and then 1.3 g of aliphatic cyclic epoxy resin was added dropwise to the reaction system, and refluxed at 110°C for 9 h. After the reaction was completed, centrifugal washing and centrifugal washing with methanol were performed, and finally dried at 100°C for 12 h to obtain modified nano-silica; (3) At room temperature, 60 g of acetone, 140 g of cyclohexanone, 10 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, then 100 g of fused silica was added, stirred for 60 min, then 100 g of fused silica was added again, stirred for 60 min, then 80 g of toughening resin, 13 g of modified nano-silica, 55 g of phenolic resin, 80 g of phosphorus-containing flame retardant were added, stirred for 60 min, finally 15 g of phosphazene and 0.1 g of accelerator were added, stirred for 120 min to obtain a high-speed copper-clad plate resin mixture.
[0032] Comparative Example 3: The difference from Example 2 is that nano-silica is directly added for modification, and the specific steps are as follows: At room temperature, 60 g of acetone, 140 g of cyclohexanone, 10 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, then 100 g of fused silica was added, stirred for 60 min, then 100 g of fused silica was added again, stirred for 60 min, then 80 g of toughening resin, 13 g of nano-silica, 55 g of phenolic resin, 80 g of phosphorus-containing flame retardant were added, stirred for 60 min, finally 15 g of phosphazene and 0.1 g of accelerator were added, stirred for 120 min to obtain a high-speed copper-clad plate resin mixture.
[0033] Comparative Example 4: The difference from Example 2 is that no nano-silica is added, and the specific steps are as follows: At room temperature, 60 g of acetone, 140 g of cyclohexanone, 10 g of BNE type epoxy resin, 15 g of DCPD type epoxy resin, 30 g of anhydride curing agent were mixed, stirred for 60 min, then 100 g of fused silica was added, stirred for 60 min, then 100 g of fused silica was added again and stirred for 60 min, then 80 g of toughening resin, 55 g of phenolic resin, 80 g of phosphorus-containing flame retardant were added and stirred for 60 min, finally 15 g of phosphazene and 0.1 g of accelerator were added, stirred for 120 min, and a high-speed copper-clad plate resin mixture was obtained.
[0034] Performance test A 7628 glass fiber cloth with a size of 31 cm*35 cm was immersed in the high-speed copper-clad plate resin mixture, and after complete immersion in the glue solution, it was baked at 185°C for 150 seconds in a dipping machine to produce a PP, which was cut into 25 cm*25 cm to obtain a prepreg. Six prepregs were stacked in a cross pattern, and copper foil was placed on top and bottom. The press was used for pressing, and the pressing and curing temperature was 220°C, the pressing time was 180 min. After pressing, the press was cooled to 70°C, and then removed and cooled to room temperature to obtain a substrate. The physical properties of the substrate were tested: Thermal expansion coefficient: using a mechanical thermal analyzer, according to IPC-TM-650 2.4.24, TMA program was selected, heating rate was 10°C / min, temperature was raised to 288°C, and held for 60 min. Select 50-100°C, analyze z-CTE1; select 200-250°C, analyze z-CTE2; select 50-260°C, analyze z-CTE3; Select data in the 60-75 min test period to analyze whether the sample is delaminated at 288°C for 60 min; According to the method specified in JISC-6471, test conditions 0.5 kg / 0.8R, record the maximum bending times; Using a universal testing machine, a 3.0 cm*15.0 cm copper-containing sample was prepared and two 3.5 mm wide copper strips were etched out using an etching machine to test the copper foil peel strength; Using a network analyzer equipped with a 10 GHz SPDR (split resonant cavity) to test the dielectric loss of the sample; According to IPC-TM-650 2.4.4, the bending strength of the substrate was tested, and the test results are shown in Table 1.
[0035] From the test results in the table, it can be seen that the high-speed copper-clad plate resin mixture prepared by the present application exhibits excellent comprehensive performance. Due to the addition of the toughening resin, the composition has good toughness, and at the same time, the thermal expansion coefficient in the range of 50-100℃ is low. This thermal expansion coefficient close to the semiconductor level indicates that the directional distribution of nano-silica effectively restricts the thermal motion of the resin matrix in the Z-axis direction. The low expansion rate in the range of 200-250℃ further verifies the dimensional stability of the material at high temperature, proving that the modified nano-silica and the resin matrix form a strong interfacial bond, effectively inhibiting the volume expansion and stress concentration at high temperature. This solves the problem of poor thermal stability and large expansion coefficient caused by the addition of toughening resin in traditional epoxy resin composition. In addition, the high peel strength reveals the excellent adhesion between the copper foil and the resin, which may be due to the formation of coordination bonding between the polyethylene glycol segments grafted on the surface of nano-silica and the copper surface. The high bending strength reflects that the material maintains high-frequency performance while still having excellent mechanical carrying capacity.
[0036] From the comparative analysis of the performance data of Example 2 and Comparative Example 1, it can be seen that the grafted material of the aliphatic ring epoxy resin exhibits a lower thermal expansion coefficient, which indicates that the introduction of the aliphatic ring structure may effectively inhibit the thermal motion of the molecular chain segment through its rigid ring configuration, and at the same time form a more intimate interfacial bond with nano-silica, thereby maintaining more stable dimensional characteristics in a wide temperature range. The higher peel strength is due to the formation of stronger chemical bonding between the active groups in the aliphatic ring epoxy resin and the copper foil surface. The improvement of the bending strength further indicates that the aliphatic ring structure has better compatibility with the resin matrix, which can more effectively transfer and disperse stress. This multi-level optimization mechanism enables the material to maintain good processing performance while obtaining more excellent thermal stability, mechanical strength and dielectric properties.
[0037] From the comparative analysis of the performance data of Example 2 and Comparative Example 2, it can be seen that the grafted material of polyethylene glycol diglycidyl ether exhibits more excellent thermal expansion characteristics, which may be due to the cross-linked network formed by the epoxy groups at the ends of polyethylene glycol and the resin matrix, which enhances the interaction force between molecular chains. At the same time, the ether bond oxygen atoms in its chain segment may form coordination with the copper foil surface. The improvement of the bending strength indicates that the grafting of polyethylene glycol diglycidyl ether may realize the toughening and reinforcing effect through the synergistic effect of its flexible chain segment and the rigid matrix of aliphatic ring epoxy resin.
[0038] From the performance data comparison and analysis of Example 2 and Comparative Examples 3 and 4, it can be seen that the addition of nano-silica and graft modification exhibit better thermal expansion inhibition effect, which may be due to the amino treatment of the silica surface active group forming chemical bonding with the resin matrix, and its two-dimensional nano structure constructing a three-dimensional heat conduction network in the matrix, effectively limiting the thermal motion of molecular chain segments. In terms of interfacial bonding performance, the introduction of modified silica significantly improves the copper foil peeling strength, and its high specific surface area characteristics enhance the mechanical interlocking effect with the resin; the improvement of dielectric properties indicates that the uniform dispersion of nano-silica may reduce the dielectric loss of the material system; the improvement of bending strength suggests that the modified nano-silica as a reinforcing phase effectively improves the carrying capacity of the matrix material through the stress transfer mechanism.
[0039] It should be understood by those of ordinary skill in the art that the above discussion of any of the embodiments is merely exemplary and is not intended to suggest that the scope of the present application is limited to these examples; under the idea of the present application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes of different aspects of the present application as described above. In order to be brief, they are not provided in detail.
Claims
1. A high-speed copper-clad laminate resin mixture, characterized in that, It is prepared from the following raw materials in parts by weight: 60 parts acetone, 140 parts cyclohexanone, 10-50 parts BNE type epoxy resin, 15-30 parts DCPD type epoxy resin, 15-30 parts acid anhydride curing agent, 200-250 parts fused silica, 30-80 parts toughening resin, 10-15 parts modified nano silica, 45-55 parts phenolic resin, 35-100 parts phosphorus-containing flame retardant, 0-15 parts phosphazene, and 0.09-0.11 parts accelerator; The preparation steps of the modified nano-silica are as follows: S1: Under a nitrogen atmosphere, nano-silica and silane coupling agent KH-550 are hydrolyzed and condensed in a mixed solution of anhydrous ethanol and deionized water to obtain aminated nano-silica. S2: Under a nitrogen atmosphere, aminated nano-silica, polyethylene glycol diglycidyl ether, and aliphatic epoxy resin undergo a ring-opening addition reaction in anhydrous ethanol to obtain modified nano-silica.
2. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The ratio of nano-silica, silane coupling agent KH-550, anhydrous ethanol, and deionized water in step S1 is 10-15g:1-1.5g:150-160mL:40-50mL.
3. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The nano-silica described in step S1 has an average thickness of <100nm, a sheet diameter of 1-3µm, and a specific surface area of 30m². 2 / g.
4. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, In step S2, the ratio of aminated nano-silica, polyethylene glycol diglycidyl ether, aliphatic epoxy resin, and anhydrous ethanol is 10-15g:2-3g:1-1.5g:200-250mL.
5. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The average molecular weight of the polyethylene glycol diglycidyl ether mentioned in step S2 is 400-500; the type of the aliphatic ring epoxy resin is ERL-4221.
6. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The BNE type epoxy resin is model CN704; the phenolic resin is model PF8020; and the toughening resin is model 97103.
7. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The anhydride curing agent is model EF-30; the fused silica is model FS1002; and the phosphorus-containing flame retardant is model PF8724.
8. The high-speed copper-clad laminate resin mixture according to claim 1, characterized in that, The phosphazene is designated as D990; the accelerator is designated as 2-MI.
9. A method for preparing the high-speed copper-clad laminate resin mixture according to claims 1-8, characterized in that, Includes the following steps: Acetone, cyclohexanone, BNE type epoxy resin, DCPD type epoxy resin, and acid anhydride curing agent are mixed and stirred. Then, molten silica, toughening resin, modified nano silica, phenolic resin, and phosphorus-containing flame retardant are added and stirred. Finally, phosphazene and accelerator are added and stirred to obtain a high-speed copper clad laminate resin mixture.
Citation Information
Patent Citations
A composition for DCPD-bisphenol type benzoxazine resin and copper clad laminate and its preparation method
CN112079978B
Halogen-free epoxy resin composition and flexible copper clad plate prepared from same
CN102101935A
Glue bonding material and preparation method thereof
CN104031588A
Halogen-free high-heat-resisting resin composition for HDI (Hexamethylene Diisocyanate) copper clad laminate
CN109504038A
Preparation method of modified silicon dioxide-epoxy resin composite slurry
CN114292614A
Cited By
Epoxy resin composition with low thermal expansion and high peel strength for high-frequency and high-speed copper-clad plate
CN122302498A